Utilization of GeoAI Applications in the Health Sector: A Review - Amponsah, Anastasia; Latue, Philia; Rakuasa, Heinrich (PT. Riset Press International, 2023)
This research describes the use of GeoAI, a geospatial data-based artificial intelligence, to improve the understanding and management of health in a global context. GeoAI enables the integration of geographic data such as maps, satellite images, and environmental information with artificial intelligence technology to analyze disease spread, health risk factors, and health resource management more accurately. This research uses a descriptive qualitative approach. The type of research used is a literature study. The literature review database used is by searching on Google Scholar, Scopus, and Google Book. The results of this study show that the basic concept of GeoAI involves more accurate spatial analysis, disease spread monitoring, disease outbreak prediction, and more efficient health resource management. However, challenges such as access to adequate data, lack of understanding among health professionals, and data privacy and security issues need to be addressed for GeoAI to be effectively implemented. In conclusion, GeoAI has great potential in improving public health and addressing global health challenges, but requires careful steps in its implementation.